2013
DOI: 10.3168/jds.2012-5761
|View full text |Cite
|
Sign up to set email alerts
|

The effect of NaCl substitution with KCl on proteinase activities of cell-free extract and cell-free supernatant at different pH levels and salt concentrations: Lactobacillus acidophilus and Lactobacillus casei

Abstract: The aim of this study was to investigate the effect of substitution of NaCl with KCl at different pH levels and salt concentrations on proteinase activity of cell-free extract and cell-free supernatant of the probiotics Lactobacillus acidophilus and Lactobacillus casei. de Man, Rogosa, and Sharpe broth aliquots were mixed with 2 pure salts (NaCl and KCl) and 2 salt concentrations at 2 concentration levels (5 and 10%), inoculated with Lactobacillus acidophilus or Lactobacillus casei, and incubated aerobically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The salt content of cheese stored in either 10% or 15% NaCl brine increased on d 1 due to the movement of Na + and Cl − ions from brine into cheese to achieve osmotic pressure balance (Ayyash et al, 2013).…”
Section: Chemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The salt content of cheese stored in either 10% or 15% NaCl brine increased on d 1 due to the movement of Na + and Cl − ions from brine into cheese to achieve osmotic pressure balance (Ayyash et al, 2013).…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…reuteri, with numbers reaching ≤6.9 log 10 cfu/mL and reductions of 0.1 to 4.4 after 28-d storage. This may have been caused by continuous diffusion of all components between the cheese matrix and its brine (Ayyash et al, 2013). The E. coli O157:H7 cells were found in both white cheese (≤2.0 log 10 cfu/g) and brine (≤1.3 log 10 cfu/mL).…”
Section: Microbial Survival In the Brinementioning
confidence: 99%
“…However, as NaCl significantly impacts the textural and sensory properties of cheese, it is difficult to completely remove it from the product. Recent studies have shown that salt concentration (ratio of sodium chloride and potassium chloride) affects the bacterial cell membrane, viability (Gandhi and others ; Gandhi and Shah ) and proteinase activity (Ayyash and others ) of common dairy bacteria. It is therefore critical to evaluate the effects of varying salt concentrations (sodium and potassium chloride) in brine solution, which impacts the activity of bacteria in cheese.…”
Section: Introductionmentioning
confidence: 99%